Etude de la Faune Malacologique de la Lagune Mellah (El-Kala - Algérie) - Farah hanane (My University, 2017)
This study analyzes the composition and distribution of benthic macrofauna in the Mellah lagoon. This brackish water ecosystem is located in Northeast Algeria within the El Kala National Park Since the late 1990s, no studies have been conducted on the Mellah benthos,. Whereas lagoonal environments are defined as fragile and especially unstable ecosystems The sampling was carried out monthly from February 2016 and July 2016 using a Van Veen bucket on 6 stations. Distributed according to a reasoned choice. The sediment was sieved on a mesh of 1 mm-2. The sorting, identification and enumeration of individuals were carried out in the laboratory.The inventory of the benthic macrofauna of Mellah revealed the presence of 8 species of which 5 Bivalves and 3 Gastropods The average density of benthic macrofauna in the lagoon amounts to 2546.66 ind.m-2 In station 4. In areas studied the numbers of species are different, between 8 and 4 most important species are Brachidontes marioni with richness varied between (73.57% and 89.33%) at the level of the different stations. Diversity or Shannon-Weaver and fairness (E) index is low since it is varied between a (0.09 - 2.014) bits and (0.032 - 0.67), respectively. Which indicates an imbalance of the Persian stands in all the stations ---------------------------------------------------------------------------------- ترتكز هده الدراسة على تحليل تكوين وتوزيع الكائنات القاعية في بحيرة الملاح. يقع هذا النظام البيئي للمياه المالحة في شمال شرق الجزائر على مستوى الحضيرة الوطنية للقالة. منذ أواخر 1990 لم تجر أي دراسات عن الكائنات البحرية للبحيرة، تتميز البحيرة بنظام بيئي هش و غير مستقر. تمت دراسة الكائنات القاعية على مستوى البحيرية ما بين الفترة الممتدة من فيفري إلى شهر جويلية 2016، تم جمع العيينات على مستوى 6 محطات تم اخدت العينات إلى المخبر أين تم فرزها بوسطه مصفات تتكون من غشاء مسامي قطره يتراوح ما بين 1-2مم و من بعد تم عدها و تصنيفها. جرد و تصنيف الكائنات القاعية مكن من تحديد 8 أنواع ، حيت تحديد 5 أنواع تتمي إلى القواقع و 3 أنواع تنتمي إلى الرخويات. الكثافة المرتفعة لللكائنات القاعية تم تحديدها على مستوى المحطة 4 بنسبة تقدر بــ 2546,66 فرد لكل متر مربع، كما أظهرت الدراسة توزيع غير متساوي للأنواع حيت سجل وجود من 8 إلى 4 أنواع على الأقل في كل محطة. مع تسجيل نسبة مرتفعة في كل المحطات لـ Brachidontes marioni بنسبة تتراوح ما بين ( 73,57% - 89,33 %) دراسة المؤشرات البيئية أظهرت قيم ضعيفة لكل من مؤشر التنوع و مؤشر التجانس حيت سجلت قيم تتراوح على التوالي بـ ( 0,09-2,01) bits و ( 0,032-0,67) , مم يدل على عدم وجود تجانس ما بين الافراد على مستوى كل المحطات تقريبا ------------------------------------------------------------------------------------ La présente étude analyse la composition et la répartition de la macrofaune benthique dans la lagune Mellah. Cet écosystème d’eau saumâtre est situé au Nord-Est algérien au sein du parc national d’El-Kala. Depuis la fin des années 1990, aucune étude n ’ avait été effectuée sur le benthos du Mellah, alors que les milieux lagunaires sont définis comme étant des écosystèmes fragiles et surtout instables. Les prélèvements ont été réalisés mensuellement de février 2016 et juillet 2016 à l’aide d’une benne Van Veen, sur 6 stations. réparties selon un choix raisonné. Le tamisage du sédiment a été effectué sur une maille de 1 mm-2. Le tri, l’identification et le dénombrement des individus ont été réalisés au laboratoire. L’inventaire de la macrofaune benthique du Mellah a révélé la présence de 8 espèces dont 5 Bivalves et 3 Gastéropodes La densité moyenne de la macrofaune benthique dans la lagune s'élève à 2546,66 ind.m-2Dans la station 4. dans zones étudies les effectifs des especes sont differents, entre 8 et 4 espèces les plus importantes sont Brachidontes marioni avec richesse variée entre (73,57% et 89,33%) au niveau des différents station. Indice de diversité ou de Shannon-Weaver et d’équitabilité (E) est faible puisqu’il est variée respectivement entre a (0,09 - 2,014) bits et (0,032- 0,67). Qui indique un déséquilibre des peuplements persques dans tous les station